1996
DOI: 10.1182/blood.v87.10.4316.bloodjournal87104316
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol ester-stimulated phosphorylation of PU.1: association with leukemic cell growth inhibition

Abstract: PU.1, a member of the ets transcription factor family, has been previously shown to be necessary for tetradecanoylphorbol-13 acetate (TPA)-induced U937 leukemic cell maturation. We examined the effects of TPA on PU.1 content and PU.1 DNA binding activity in U937 cells. Unstimulated cells expressed PU.1 mRNA transcripts and TPA did not increase these levels. However, TPA treatment induced phosphorylation of PU.1. Gel-shift analysis using a labeled PU.1 oligomer showed that TPA induced a unique PU.1 binding acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 31 publications
3
18
1
Order By: Relevance
“…To confirm the above observation experimentally, by detecting molecular markers indicative of macrophage differentiation, we conducted an EMSA study on DNA-binding activity of PU.1 protein, which is a key regulator of macrophage differentiation. It has been reported that TPA-induced growth inhibition of U937 cells is associated with phosphorylation of PU.1 and generation of unique PU.1-binding activity [23]. Although we could confirm the results of this previous study on the effect of TPA, we could not find any effect of arsenite on the DNA-binding activity of PU.1.…”
Section: Discussioncontrasting
confidence: 93%
“…To confirm the above observation experimentally, by detecting molecular markers indicative of macrophage differentiation, we conducted an EMSA study on DNA-binding activity of PU.1 protein, which is a key regulator of macrophage differentiation. It has been reported that TPA-induced growth inhibition of U937 cells is associated with phosphorylation of PU.1 and generation of unique PU.1-binding activity [23]. Although we could confirm the results of this previous study on the effect of TPA, we could not find any effect of arsenite on the DNA-binding activity of PU.1.…”
Section: Discussioncontrasting
confidence: 93%
“…In contrast, exposure to bryostatin 1 did not have an inhibitory effect on cell proliferation. Consistent with the results of previous studies [7,27], co-administration of bryostatin 1 reduced the growth-inhibitory effects of PMA (data not shown).…”
Section: Growth and Differentiation Of U937 Cellssupporting
confidence: 92%
“…In human promyelocytic leukemia cells (HL-60), bryostatin 1 variably induces maturation [29,43]; moreover, it blocks PMA effects in sublines immune to its differentiation-inducing actions [27]. In the human monocytic leukemic cell line U937, bryostatin 1 has been reported to exert antiproliferative effects by some investigators [4], although others have found its activity to be marginal, and consistently less than that exerted by PMA [7,36]. Recently, the antiproliferative effects of bryostatin 1 toward U937 cells has been related to dehosphorylation (and inactivation) of cyclin-dependent kinase-2 (CDK2), although such effects were most pronounced at relatively high bryostatin 1 concentrations (e.g., 200 nM) [4].…”
Section: Introductionmentioning
confidence: 99%
“…(35,45) Intriguingly, however, supraphysiologic levels of Pu.1 expression do not necessarily correlate with increased myelomonocytic lineage commitment. In fact, recent studies suggest that phosphorylation of Pu.1 plays a central role in modulating its DNA binding affinity, (37,46) and is thereby critical to its ability to activate myeloid-specific gene programs that promote terminal differentiation. (39,40) For instance, although human myeloid leukemic cell lines have been shown to overexpress Pu.1, (47) the transcript levels of Pu.1-dependent myeloid genes, such as CD11b and c-fms, are relatively low by comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of Pu.1 is known to retard its migration in SDS-PAGE electrophoresis. (36,37) To confirm that these band shifts represent phosphorylated forms of Pu.1, nuclear lysates were treated with potato acid phosphatase prior to electrophoresis. Phosphatase treatment resulted in complete conversion of the shifted bands to the lower molecular weight, unphosphorylated Pu.1 species (Fig.…”
Section: Conditional Nf1 Haploinsufficiency In Mp Cells Promotes Expamentioning
confidence: 99%